Pelatihan Pencatatan Laporan Keuangan Sederhana Pada Santri Pondok Pesantren Luqman Hakim - Meike Ardhana Reswari; Muninggar; Windy Fatmawati; Hendri Hermawan Adinugraha; Ade Gunawan (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Accounting can be found anywhere and by anyone. Recording financial statements is an important activity in accounting. Financial statements are not only needed by companies but also by individuals. Santri becomes part of accounting by recording monthly money management. Santris have difficulty recording financial reports clearly, in detail, and systematically. The purpose of the service is to train students to record simple financial reports in managing money. The service team used a training method through four stages. Material exposure, training accompanied by direct assistance, discussion-question, answer, and evaluation. The service was carried out at Luqman Hakim Islamic boarding school in Rowolaku village on May 24, 2023, at 15.00 WIB by 10 santris. The results of this training were that the santri participated in the training enthusiastically. The delivery of material is light, according to needs, and easy to understand, with direct training assistance, exciting discussions, sufficient training duration, and evaluation through questionnaires as a measure of success. Santri was helped and able to record simple financial reports. This is an effort to manage santri finances and minimize waste. Financial reports help students organize finances clearly and systematically so that it is clear between money and needs in a certain period.